America's working women: A documentary history, 1600 to the present - Baxandall, (1939- ...)., Rosalyn Fraad; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Accessible en ligne : https://archive.org/details/isbn_9780393312621
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

La vague antiféministe - Institut de recherches et d'études féministes (FéminÉtudes, 1995)
Cette publication porte sur la nécessité d’être féministe en 1995 et sur l’histoire de l’antiféminisme à la fin du XXe siècle. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Disponible en libre accès : https://iref.uqam.ca/feminetudes/test/
Keywords: 1900-1999; 1990-1999; amériques; antiféminisme; approches et analyses; droits des femmes*; féminétudes; histoire et politique; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques

Defending pornography: free speech, sex, and the fight for women's rights - Strossen, Nadine (Scribner, 1995)
This book examines a key question that has divided feminists for decades: is censoring pornography good or bad for women? The book makes a powerful case that increasing government power to censor sexual expression, beyond the limits that the First Amendment sensibly permits (for example, outlawing child pornography) would do more harm than good for women and others who have traditionally been marginalized due to sex or gender. The book explains how the very anti-porn laws pushed by some feminists have led to the censorship of LGBTQ+ and feminist works, and it examines the startling connections between anti-porn feminists and right-wing fundamentalists. The book lays out the multiple current assaults on sexual expression, which continue to come from across the ideological spectrum. It shows that freedom for such expression remains an essential prerequisite for the equality, safety, and dignity of women and sexual/gender minorities.
Section: 320 p. : ill. ; 22 cm
Keywords: amériques; cours; discipline; droit; droits des femmes*; liberté d'expression; pornographie; premier cycle; régions géographiques; science politique et droit; sex wars; sex1911; thématiques; états-unis